2022
DOI: 10.1186/s13012-022-01244-1
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of measurement-based care implementation in community mental health settings: results from a mixed-methods evaluation

Abstract: Background Tailored implementation approaches are touted as superior to standardized ones with the reasoning that tailored approaches afford opportunities to select strategies to resolve determinants of the local context. However, results from implementation trials on this topic are equivocal. Therefore, it is important to explore relevant contextual factors that function as determinants to evaluate if they are improved by tailoring and subsequently associated with changes in implementation out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…In this trial, increases in first-level leaders’ use of implementation leadership by 4-month post-baseline explained 82% of LOCI’s effect on improvement in clinic implementation climate by 12-month post-baseline. This finding aligns with qualitative data from another recent trial of MBC implementation in community mental health [ 93 ], which also found that leader and clinical supervisor support for MBC were perceived as key implementation mechanisms. The linkage of implementation leadership to improvement in clinic implementation climate suggests implementation leadership behaviors are important targets for implementation success.…”
Section: Discussionsupporting
confidence: 88%
“…In this trial, increases in first-level leaders’ use of implementation leadership by 4-month post-baseline explained 82% of LOCI’s effect on improvement in clinic implementation climate by 12-month post-baseline. This finding aligns with qualitative data from another recent trial of MBC implementation in community mental health [ 93 ], which also found that leader and clinical supervisor support for MBC were perceived as key implementation mechanisms. The linkage of implementation leadership to improvement in clinic implementation climate suggests implementation leadership behaviors are important targets for implementation success.…”
Section: Discussionsupporting
confidence: 88%
“…Research has shown that tailoring implementation strategies to address high-priority implementation barriers can increase MBC fidelity, at least with respect to one element: routine administration of measures symptoms, outcomes, and processes before therapy sessions [ 11 13 ]. Our experience suggests, however, that for tailored implementation to realize its full potential, new methods are needed for identifying and prioritizing implementation barriers and matching strategies to high-priority barriers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%